Caracterización de UWB y WiFi FTM en obras - Álvarez-Merino, Carlos Simón; Luo Chen, Hao Qiang; Llanes Michel, Joel; Khatib, Emil Jatib; Barco-Moreno, Raquel (My University, 2022)
The construction industry is one of the largest sectors not having a major movement towards digitalisation. For this reason, in recent years, there is an effort for stimulating innovation in the construction site mainly to improve the safety of workers. Thanks to precise, real-time location, workers can be monitored to minimise risks and avoid disasters. For this reason, in this paper ultra-wideband (UWB) and WiFi Fine Time Measurement (FTM) localisation technologies are characterised for this type of environment.
Keywords: Construcción -- Medidas de seguridad; Construcción -- Innovaciones tecnológicas; UWB; WiFi; construction; localization; fusion